Xylanases, Cellulases, and Acid Protease Produced by Stenocarpella maydis Grown in Solid-state and Submerged Fermentation - Edna María Hernández-Domínguez; Rosario Ared Rios-Latorre; Jorge Álvarez-Cervantes; Octavio Loera-Corral; Alma Delia Román-Gutiérrez; Gerardo Díaz-Godínez; Yuridia Mercado-Flores (BioResources, 2014)
Activity levels of extracellular hydrolytic enzymes produced by Stenocarpella maydis, a fungal pathogen of maize, have so far not been reported. Production of xylanase, cellulase, and acid protease by this ascomycete using different culture media in solid-state and submerged fermentation was studied. In solid-state fermentation, polyurethane foam was used as an inert support, and corncob, corn leaves, and broken corn were used as biodegradable supports. The highest xylanase activity was produced in the medium with xylan in both fermentation systems, reaching 18,020 U/L and 19,266 U/L for submerged and solid-state fermentation, respectively. Cellulase production was observed only in the culture medium with carboxymethylcellulose, obtaining values of 7,872 U/L in submerged fermentation and 9,439 U/L in solid-state fermentation. The acid protease was produced only in minimal medium with glucose in acidic pH, reaching the highest levels of activity in SSF (806 U/L). The corncob was the best biodegradable support for the production of xylanases and acid protease. Two isoenzymes of xylanase and cellulase were observed in both fermentation systems, and three isoenzymes of xylanase were produced on the biodegradable supports.